Development and Properties of Electrospun Collagen-chitosan Nanofibrous Membranes as Skin Wound Healing Materials (Journal of Fiber Bioengineering and Informatics, 2014)
The objective of this study was to develop an original anti-bacterial material for skin wound healing.Collagen-chitosan nanofibrous membranes were fabricated by electrospinning. The morphology, tensilestrength and contact angle of the membranes were measured. In addition, cell adhesion and proliferationon the membranes were evaluated. The antimicrobial property against Staphylococcus aureus of themembranes was also determined. The results indicated that the diameter of electrospun collagen-chitosannanofibrous membranes was 221 ± 105 nm, the tensile strength was 1.53 ± 0.12 Mpa and the contact anglewas 42.44 ± 4.03 ° . Besides, the collagen-chitosan nanofibrous membranes promoted cell attachment andproliferation and also inhibited the growth of Staphylococcus aureus. In conclusion, these data suggestthat electrospun collagen-chitosan nanofibrous membranes have potential to serve as skin wound healingmaterials, which might be ascribed to its favorable mechanical strength, excellent cell affinity, as well asgood antimicrobial properties against Staphylococcus aureus.
Keywords: Collagen; Chitosan; Nanofibers; L929 Cell